HUBUNGAN TOTAL TES DENGAN RASIO POSITIF (POSITIVITY RATE) COVID-19 - Jalin Paluhutan Sitompul; Ascobat Gani (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The Corona Virus That Causes COVID-19 Has Infected More Than 917,015 People In Indonesia And Continues To Increase, Especially Since The Signs Of The Pandemic Subside Have Not Yet Come To Light. In Addition To Vaccination For The Community To Create Herd Immunity, To Accelerate The Completion Of COVID-19 Cases In Indonesia, The Application Of The 3T (Testing, Tracing, Treatment) System Is Still One Solution In Overcoming The COVID-19 Pandemic. The Correct Application Of The 3T System Will Get Valid Data On The Number Of People Diagnosed With COVID-19 And Can Determine The Areas With A Lot Of Covid-19 Diagnoses. This Study Aims To Obtain Analytical Results That Confirm The Relationship Between The Number Of People Tested And A Decrease In The Positive Ratio Of COVID-19. The Method Used Is The Ordinary Least-Square (OLS) Panel Data Method Where This Method Is A Two-Dimensional Regression To Determine The Relationship Between The Dependent Variable And The Independent Variable. The Results Obtained Can Explain The Close Relationship Between The Number Of People Tested And The Positive Ratio, Where From The Estimation Results The Pooledols Value Gets A P-Value <0.005 Or 2.76e-6, The Test Regression Coefficient Shows A Value Of -0.03493 And An R-Square Value Of 0.4306 Which Means That There Is A Negative Relationship Between The Number Of People Tested With A Positive Ratio And The Influence Of The Relationship Between The Two Variables Is Sufficient But Not Too Strong. From The Results, It Was Found That The More Number Of Tests Carried Out Will Be Able To Reduce The Exposure Of People Affected By COVID-19 Â  Keywords:(Positivityrate),COVID-19,Total Tes